Pemberdayaan Masyarakat melalui Pengolahan Jerami Padi Peram dengan Penambahan Mineral - Ananta, Dwi; Andri, Andri; Yelita, Yulia; Khalil, Khalil (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Limited access to quality feed remains a major constraint in smallholder livestock systems, particularly due to the low nutritional value of untreated rice straw. To address this challenge, a community empowerment program was implemented to enhance farmers’ knowledge and skills in processing mineral-enriched fermented rice straw as an alternative feed. Using a participatory approach, the program involved technical training, hands-on demonstrations, and five months of field mentoring with 25 participants from the Kelompok Tani Lereng Sago. Evaluation through pre- and post-tests showed a significant improvement in knowledge, with average scores rising from 60 to 85. Supplementation with fermented rice straw increased average daily weight gain from 200–350 g to 555 g/head/day. Reproductive performance also improved: service per conception (S/C) decreased from 3.5 to 1.8, conception rate rose from 40% to 65%, and pregnancies doubled. Participant satisfaction averaged 4.66 on a 5-point Likert scale, indicating strong acceptance. The results confirm that this locally adapted and low-cost feed innovation is effective in improving cattle productivity and farmer capacity. The empowerment model developed offers high potential for replication in similar rural livestock systems.